Advance Recruitment System - Joshi, HU; Patil, GR; Singanjude, YB; Dhote, AN; Adhav, MS (International Journal of Computer Sciences and Engineering, 2025)
Our research goal is to develop an advance web portal system which is efficient in the evolution of recruitment system. This system is effectual for the Recruiter for Recruiting the job aspirants which are worthy for the respective job and the job aspirants can also apply for job position posted on the portal as well as the job aspirant can Search for the specific Job Position as their preferences. Thus, only the specific mail on the basis of their preferences should be sent, no other job position mail should be sent. This system maintains a trustworthy relation with the job aspirants and the recruiter by verifying the company is actually exist or not. It’s also check whether the job aspirants have all the skills mention in his resume. A survey conducted for measuring the problem faced by the students on existing Job Portal System and after that the idea for the Advance Recruitment System is enacted.